Paramedic students' confidence and satisfaction with clinical simulations of an emergency medical care programme in South Africa: A cross-sectional study - Peter T. Sandy; John T. Meyer; Oluwaseun S. Oduniyi; Azwihangwisi H. Mavhandu-Madzusi (AOSIS, 2021)
Background: There has been an increase in the use of clinical simulations as instructional tools in healthcare education. This is because of their role in ensuring patients' safety and quality-care provision. Aim: This study investigated the paramedic students' satisfaction and self-confidence in the clinical simulation of an emergency medical care programme. Setting: The study was conducted at the Durban University of Technology in the KwaZulu-Natal Province of South Africa. The paramedic students' satisfaction and self-confidence in the clinical simulation of an emergency medical care programme were the focus of the study. Methods: The study used a cross-sectional research design. A convenience sampling method was used to select the 83-paramedic students who participated in the study. Data were collected between July and September 2017 using a structured questionnaire. Descriptive statistics (frequencies and percentages and Spearman's rank-order correlation coefficient) and an inferential test, ordinal logistic regression analysis, were used for data analysis. Results: High levels of paramedic students' satisfaction and self-confidence in simulation activities were reported. Generally, the paramedic students' demographics were associated with the satisfaction and self-confidence variables with p-values ≤ 0.04. Emergency medical care training undertaken by the paramedic students was significantly associated with self-confidence (p = 0.00). Conclusion: Clinical simulation can bridge the theory-practice gap for paramedic students. It is a hands-on approach that promotes students learning of clinical skills through reflection.